2003
DOI: 10.1073/pnas.0437946100
|View full text |Cite
|
Sign up to set email alerts
|

An α-syntrophin-dependent pool of AQP4 in astroglial end-feet confers bidirectional water flow between blood and brain

Abstract: The water channel AQP4 is concentrated in perivascular and subpial membrane domains of brain astrocytes. These membranes form the interface between the neuropil and extracerebral liquid spaces. AQP4 is anchored at these membranes by its carboxyl terminus to ␣-syntrophin, an adapter protein associated with dystrophin. To test functions of the perivascular AQP4 pool, we studied mice homozygous for targeted disruption of the gene encoding ␣-syntrophin (␣-Syn ؊/؊ ). These animals show a marked loss of AQP4 from pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
416
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 474 publications
(463 citation statements)
references
References 26 publications
32
416
1
1
Order By: Relevance
“…For example, immunoelectron microscopy showed that the absence of a-syntrophin dramatically altered the localization pattern of AQP4 but not Kir4.1 in hippocampal astrocytes (Amiry-Moghaddam et al, 2003a). Similar evidence has been proposed in retinas from a-syntrophin null mice where the localization of AQP4 was marginally decreased in M€ uller cell endfeet and perivascular processes, whereas Kir4.1 localization was unaffected (Frydenlund et al, 2004).…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…For example, immunoelectron microscopy showed that the absence of a-syntrophin dramatically altered the localization pattern of AQP4 but not Kir4.1 in hippocampal astrocytes (Amiry-Moghaddam et al, 2003a). Similar evidence has been proposed in retinas from a-syntrophin null mice where the localization of AQP4 was marginally decreased in M€ uller cell endfeet and perivascular processes, whereas Kir4.1 localization was unaffected (Frydenlund et al, 2004).…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, AQP4 was shown to interact with the DGC in M€ uller cells (Dalloz et al, 2003) and brain astrocytes (Amiry-Moghaddam et al, 2003aNeely et al, 2001). Based on this evidence, experiments were conducted to examine whether AQP4 can interact with DGC proteins and also with Kir4.1 in retina.…”
Section: Aqp4 Interacts With Kir41 and Dgc In Retinamentioning
confidence: 99%
See 3 more Smart Citations